Implementasi Perlindungan Hukum terhadap Korban Tindak Pidana Perdagangan Orang dalam Putusan Nomor 1614/Pid.Sus/2021/PN Tng - Nira Firnanda; Yudi Rijali Muslim; Fikry Latukau (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study analyzes legal protection for human trafficking victims in Decision Number 1614/Pid.Sus/2021/PN Tng, using Law Number 21 of 2007 and Law Number 3 of 2026 on Witness and Victim Protection as a contemporary benchmark. Normative legal analysis shows that the decision punished the offenders but did not order restitution, rehabilitation, or victim recovery. Analysis of legal substance, structure and culture identifies weak recovery integration, limited coordination and an offender-centered orientation. The ratio decidendi satisfies legality but does not fully reflect substantive justice for victims. Therefore, strengthening victim protection and recovery mechanisms through the application of restitution, rehabilitation and more effective inter-agency coordination within the criminal justice process is essential.